Study of Structure, Classification And Functions Of Carbohydrates - SHAHZADA, Dr.M.Z; Equbal, Md. Danish (Innovative Research Thoughts, 2017)
Carbohydrates, together with lipids, proteins and nucleic acids, are one of the four major classes of biologically essential organic molecules found in all living organisms. Carbohydrates, all coming from the process of photosynthesis, represent the major part of organic substance on Earth, are the most abundant organic components in the major part of fruits, vegetables, legumes and cereal grains, carry out many functions in all living organisms and are the major energy source in a Mediterranean-type diet. Finally, they provide flavor and texture in many processed foods.